Toward more reflexive, empowering, and ethical metaphorical organizational research. Issue 5 (November 2017) - Driver, Michaela
This study aims to take forward Gareth Morgan's call for more reflexivity and self-deconstruction in metaphorical organizational research by developing a novel framework for the production and use of metaphors. Drawing on psychoanalytic theorizing, this framework seeks to move the field toward an approach to metaphors in which metaphors can be explored as symptoms of our struggles with unconscious desire. This, in turn, offers opportunities for engaging in more reflexive, empowering, and ethical metaphorical research.